RARE-11. EFFICACY AND SAFETY OF DABRAFENIB + TRAMETINIB IN PATIENTS WITH RECURRENT/REFRACTORY BRAF V600E–MUTATED LOW-GRADE GLIOMA (LGG). (5th November 2018) - Wen, Patrick; De Greve, Jacques; Mason, Warren; Hofheinz, Ralf-Dieter; Dietrich, Sascha; de Vos, Filip; van den Bent, Martin; Mookerjee, Bijoyesh; Boran, Aislyn; Burgess, Paul; Rangwala, Fatima; Gazzah, Anas
Abstract: BACKGROUND: Approximately 9%-18% of LGGs possess BRAF V600E mutations. Combined BRAF and MEK inhibition is efficacious in BRAF V600–mutated melanoma, lung cancer, and anaplastic thyroid cancer. Dabrafenib (BRAF inhibitor) + trametinib (MEK inhibitor) was evaluated as treatment for patients with recurrent/refractory BRAF V600E–mutated LGG. METHODS: In this phase 2, open-label trial (NCT02034110), patients with BRAF V600E mutations in 9 rare tumor types, including LGG, received continuous dabrafenib (150 mg BID) + trametinib (2 mg QD) until unacceptable toxicity, disease progression, or death. For the LGG cohort, eligible patients had histologically confirmed recurrent or progressive WHO grade 1 or 2 glioma that was refractory to standard-of-care therapies. The primary endpoint was investigator-assessed overall response rate (ORR) by RANO criteria. Secondary endpoints included duration of response (DOR), progression-free survival (PFS), overall survival (OS), and safety. RESULTS: Nine patients with LGG had enrolled at data cutoff (3 January 2018). Eight of 9 patients were evaluable for response. Median age was 33 years. Eight of 9 patients had received prior surgery. Investigator-assessed confirmed ORR was 50% (4/8; 95% CI, 16%-84%), with 3 of 4 responses ongoing at data cutoff. Two of 4 patients had a DOR of ≥ 18 months. The PFS and OS Kaplan-Meier estimates at 18 months were 50% (95% CI, 15%-78%) and 86% (95% CI, 33%-98%), respectively. Adverse events (AEs) in patients with LGG included fatigue (67%), headache (67%), arthralgia, nausea, and pyrexia (56% each). Grade 3/4 AEs included fatigue (22%), arthralgia, headache, and diarrhea (11% each). Biomarker analyses are ongoing and will be presented. CONCLUSIONS: Dabrafenib + trametinib demonstrated promising efficacy in patients with recurrent/refractory BRAF V600E-mutated LGG, with manageable AEs and no new safety signals